Emerging concepts regarding pannexin 1 in the vasculature - Good, Miranda E. (Biochem Soc Trans, 2015)
Pannexin channels are newly discovered ATP release channels expressed throughout the body. Pannexin 1 (Panx1) channels have become of great interest as they appear to participate in a multitude of signalling cascades, including regulation of vascular function. Although numerous Panx1 pharmacological inhibitors have been discovered, these inhibitors are not specific for Panx1 and have additional effects on other proteins. Therefore, molecular tools, such as RNA interference and knockout animals, are needed to demonstrate the role of pannexins in various cellular functions. This review focuses on the known roles of Panx1 related to purinergic signalling in the vasculature focusing on post-translational modifications and channel gating mechanisms that may participate in the regulated release of ATP.